Ідентифікація генів – промоторів остистості в інтрогресивної лінії Triticum aestivum / Aegilops umbellulata - Антонюк, М.З.; Прокопик, Д.О.; Мартиненко, В.С.; Терновська, Т.К. (Цитология и генетика, 2012)
Виконано генетичний аналіз інтрогресивних ліній Triticum aestivum/Aegilops umbellulata щодо ознаки остистість колоса. За даними вивчення ліній та гібридів за остистістю та спектрам мікросателітних компонентів запропоновано дигенну модель контролю ознаки з геном – інгібітором остистості В1 (5AL) та геном – промотором остистості Awn1, локалізованим у хромосомі 6U егілопсу зонтичного. Хромосома 5А остистої лінії перебудована відносно такої хромосоми генотипу Аврора, і відстань між SSR-локусом Xwmc705-5AL та перебудованим фрагментом чи локусом В1/b1 визначено як 15,5 сМ. Выполнен генетический анализ интрогрессивных линий Triticum aestivum/Aegilops umbellulata по признаку остистость колоса. По данным изучения линий и гибридов по остистости и спектрам микросателлитных компонентов предложена дигенная модель контроля признака с геном – ингибитором остистости В1 (5AL) и геном – промотором остистости Awn1, локализованным в хромосоме 6U эгилопса зонтичного. Хромосома 5А остистой линии перестроена относительно этой же хромосомы генотипа Авроры, и расстояние между SSR-локусом Xwmc705-5AL и перестроенным фрагмен-том или локусом В1/b1 определено как 15,5 сМ. Выполнен генетический анализ интрогрессивных линий Triticum aestivum/Aegilops umbellulata по признаку остистость колоса. По данным изучения линий и гибридов по остистости и спектрам микросателлитных компонентов предложена дигенная модель контроля признака с геном – ингибитором остистости В1 (5AL) и геном – промотором остистости Awn1, локализованным в хромосоме 6U эгилопса зонтичного. Хромосома 5А остистой линии перестроена относительно этой же хромосомы генотипа Авроры, и расстояние между SSR-локусом Xwmc705-5AL и перестроенным фрагментом или локусом В1/b1 определено как 15,5 сМ. Genetic analysis of Triticum aestivum/Aegilops umbellulata introgressive line for the character ear awnedness has been realized. According to the studying the lines and hybrids for the characters awnedness and electrophoresis spectra of microsatellite components the digenic model for control of awnedness is suggested. The model supposes participation of gene – inhibitor of awnedness В1 (5AL) and gene – promoter of awnedness Awn1 in chromosome 6U of Aegilops umbellulata. Chro-mosome 5А of the awned line is rearranged relative to the same chromosome of the Aurora genotype. The distance between the Xwmc705-5AL SSR-locus and rearranged fragment or locus В1/b1 is determined as 15,5 сМ. Genetic analysis of Triticum aestivum/Aegilops umbellulata introgressive line for the character ear awnedness has been realized. According to the studying the lines and hybrids for the characters awnedness and electrophoresis spectra of microsatellite components the digenic model for control of awnedness is suggested. The model supposes participation of gene – inhibitor of awnedness В1 (5AL) and gene – promoter of awnedness Awn1 in chromosome 6U of Aegilops umbellulata. Chromosome 5А of the awned line is rearranged relative to the same chromosome of the Aurora genotype. The distance between the Xwmc705-5AL SSR-locus and rearranged fragment or locus В1/b1 is determined as 15,5 сМ.